2021
DOI: 10.3390/cancers13112695
|View full text |Cite
|
Sign up to set email alerts
|

STING Agonists as Cancer Therapeutics

Abstract: The interrogation of intrinsic and adaptive resistance to cancer immunotherapy has identified lack of antigen presentation and type I interferon signaling as biomarkers of non-T-cell-inflamed tumors and clinical progression. A myriad of pre-clinical studies have implicated the cGAS/stimulator of interferon genes (STING) pathway, a cytosolic DNA-sensing pathway that drives activation of type I interferons and other inflammatory cytokines, in the host immune response against tumors. The STING pathway is also inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
175
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(197 citation statements)
references
References 123 publications
(146 reference statements)
0
175
0
2
Order By: Relevance
“…The activation of immune cells after DMXAA application is mainly related to the protein STING (stimulator of interferon genes). The pathway associated with the STING protein is a relatively new direction of research in cancer therapy [63]. It is well known that immune cells' activation using STING agonists mediates the innate immune response, which is responsible for the therapeutic effect [21,64].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of immune cells after DMXAA application is mainly related to the protein STING (stimulator of interferon genes). The pathway associated with the STING protein is a relatively new direction of research in cancer therapy [63]. It is well known that immune cells' activation using STING agonists mediates the innate immune response, which is responsible for the therapeutic effect [21,64].…”
Section: Discussionmentioning
confidence: 99%
“…The cGAS-STING signaling in cancer cells is an increasingly recognized and important mechanism connecting genome instability to immune cell infiltration and inflammation in neoplastic malignant tumors [ 210 ]. Subsequently, tumor cells frequently impair cGAS-STING signaling to evade immune surveillance [ 211 , 212 , 213 ]. Thus, agonists are being developed to restore and to enhance cGAS-STING activity and the subsequent antitumor immune response in cancer treatment [ 212 ].…”
Section: Cancermentioning
confidence: 99%
“…Subsequently, tumor cells frequently impair cGAS-STING signaling to evade immune surveillance [ 211 , 212 , 213 ]. Thus, agonists are being developed to restore and to enhance cGAS-STING activity and the subsequent antitumor immune response in cancer treatment [ 212 ]. It should be noted, however, that the immune response to cancer cells including the cGAS-STING signaling, is complex and an extensive review of the current state of the field is beyond the scope of this Review.…”
Section: Cancermentioning
confidence: 99%
“…An increasing number of investigations have shown that STING is involved in various diseases; the activation of STING can develop as cancer therapeutics. However, the activation of STING can also induce inflammatory responses and lead to inflammatory injury ( Amouzegar et al, 2021 ; Decout et al, 2021 ). The activation of STING is associated with inflammatory diseases such as acute pancreatitis, sepsis, and rheumatoid arthritis ( Jeremiah et al, 2014 ; Heipertz et al, 2017 ; Zhao et al, 2018 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%